2011
DOI: 10.1186/1748-717x-6-150
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pathological tumor stage for salvage radiotherapy after radical prostatectomy in patients with prostate-specific antigen < 1.0 ng/ml

Abstract: BackgroundTo evaluate prognostic factors in salvage radiotherapy (RT) for patients with pre-RT prostate-specific antigen (PSA) < 1.0 ng/ml.MethodsBetween January 2000 and December 2009, 102 patients underwent salvage RT for biochemical failure after radical prostatectomy (RP). Re-failure of PSA after salvage RT was defined as a serum PSA value of 0.2 ng/ml or more above the postradiotherapy nadir followed by another higher value, a continued rise in serum PSA despite salvage RT, or initiation of systemic thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Approximately one-third of patients with BRec after RP will have distant metastases, and the median time to the development of distant metastases following BRec is 8 years [3]. Salvage radiation therapy (SRT) has been reported as an effective treatment for BRec after RP [4][5][6][7][8][9][10][11][12][13][14][15][16]. Reports have varied regarding prognostic factors for biochemical control after SRT.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately one-third of patients with BRec after RP will have distant metastases, and the median time to the development of distant metastases following BRec is 8 years [3]. Salvage radiation therapy (SRT) has been reported as an effective treatment for BRec after RP [4][5][6][7][8][9][10][11][12][13][14][15][16]. Reports have varied regarding prognostic factors for biochemical control after SRT.…”
Section: Introductionmentioning
confidence: 99%
“…In this meta-analysis, eight studies evaluated the surgical margins910131416171920 However, the overall effect showed no significant association between surgical margins and BCR (OR: 1.09; 95% CI: 0.83–1.43). The fixed-effects model was reported here because there was no evidence of heterogeneity ( I 2 = 30%) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 86%
“…In this meta-analysis, we evaluated three studies including 264 patients that evaluated radiation dose 141519. Pooling of data from these studies showed a significant effect of radiation dose ≥64 Gy versus the controls (OR: 0.35; 95% CI: 0.19–0.64).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations